INTERNALIZING INCLUSIVE ISLAMIC VALUES AT MUSLIM OI BURA: A COUNSELING CONCEPTUAL - Atiyah, Kanzul; Sa'adah, Nurus (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
Islam openly accepts differences in human beliefs on this earth. According to Islam, diversity is considered a necessity, so differences in beliefs are also normal. However, the social reality that occurs is that there are still practices of religious discrimination in society, such as the case of religious discrimination carried out by a group of Muslims in Tambora against local Hindus. This article aims to develop the concept of counseling as an effort to handle problems. The research method used is a literature study with data collection techniques from books and journal articles. This research produces the concept of a counseling group approach using the REBT technique as an alternative to eliminating negative prejudices that hinder the birth of tolerance. The REBT technique used also adopts Islamic values. This step aims to suppress irrational beliefs by refreshing the meaning of inclusive Islam. In the process, it is hoped that it will be able to support the formation of an attitude of tolerance in the Muslim community in Tambora.